2020
DOI: 10.1016/j.atherosclerosis.2019.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the characteristics at diagnosis and treatment of children with heterozygous familial hypercholesterolaemia (FH) from eight European countries

Abstract: The age of HeFH diagnosis varies significantly between 8 European countries. • The proportion of HeFH children being treated varies across 8 European countries. • A quarter of FH children on statins have LDL-C above the target (> 3.5 mmol/L). • Many FH children are not getting the full benefit of early diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 38 publications
2
44
0
1
Order By: Relevance
“…The overall increase in statin use in all three countries among children aged 10-14 years is therefore reassuring, whereas the lack of increase in statin use among children aged 15-19 years in Denmark should be further investigated. We did not observe differences in statin use between sexes in any of the countries, which is in line with data from the UK Paediatric FH register [10], whereas other countries have found slightly higher on-treatment rates in boys [11]. Although there may be reasons for not treating some children with FH [1,12], the treatment rates in our study are too low, particularly in Sweden and Denmark.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The overall increase in statin use in all three countries among children aged 10-14 years is therefore reassuring, whereas the lack of increase in statin use among children aged 15-19 years in Denmark should be further investigated. We did not observe differences in statin use between sexes in any of the countries, which is in line with data from the UK Paediatric FH register [10], whereas other countries have found slightly higher on-treatment rates in boys [11]. Although there may be reasons for not treating some children with FH [1,12], the treatment rates in our study are too low, particularly in Sweden and Denmark.…”
Section: Discussionsupporting
confidence: 88%
“…Based on aggregate data from Norway, we observed a strong correspondence between the number of statin users and the number of individuals with genetically verified FH between 2008 and 2018. This could indicate that to increase treatment rates, more children need to be genetically diagnosed with FH, as supported by Leren et al [13] and an European study where countries with the highest percentage of children identified with an FH mutation also had the highest percentage on statin treatment (such as Greece and The Netherlands) [11]. However, we cannot claim any causal relation in this study, and studies of data at an individual level are warranted to adequately address the association between statin use and genetically verified FH.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…В 2019 г. опубликованы результаты исследования, проведенного в 8 европейских странах (Норвегия, Великобритания, Чехия, Португалия, Греция, Австрия, Нидерланды, Бельгия), посвященного сравнению тактики и результатов лечения семейной гиперхолестеринемии в общей выборке из 3064 детей. Показано, что доля детей, принимающих статины, увеличивается с возрастом и к 15-летнему возрасту уже 79% пациентов в этих странах принимают статины [39]. Цели для детей старше 10 лет состоят в достижении уровня ЛПНП <3,5 ммоль/л (<135 мг/дл), в младшем возрасте -снижении этого показателя на ≥50%.…”
Section: обзоры литературыunclassified